2014
DOI: 10.1038/ncomms5446
|View full text |Cite
|
Sign up to set email alerts
|

Host iron status and iron supplementation mediate susceptibility to erythrocytic stage Plasmodium falciparum

Abstract: Iron deficiency and malaria have similar global distributions, and frequently co-exist in pregnant women and young children. Where both conditions are prevalent, iron supplementation is complicated by observations that iron deficiency anaemia protects against falciparum malaria, and that iron supplements increase susceptibility to clinically significant malaria, but the mechanisms remain obscure. Here, using an in vitro parasite culture system with erythrocytes from iron-deficient and replete human donors, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 43 publications
(57 reference statements)
8
121
0
1
Order By: Relevance
“…Clinicians monitored children's health statuses during sick visits and at routine visits occurring on a biweekly basis during the first 12 months of life and a monthly basis for any follow-up beyond the first year. Children's hemoglobin was measured at sick visits and during routine visits at approximately 3,6,12,18,24,30,36,42, and 48 months of age. Parasitemia by P. falciparum was determined after counting 200 leukocytes on Giemsa-stained thick blood smear of a sample collected by heel or finger prick during child visits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians monitored children's health statuses during sick visits and at routine visits occurring on a biweekly basis during the first 12 months of life and a monthly basis for any follow-up beyond the first year. Children's hemoglobin was measured at sick visits and during routine visits at approximately 3,6,12,18,24,30,36,42, and 48 months of age. Parasitemia by P. falciparum was determined after counting 200 leukocytes on Giemsa-stained thick blood smear of a sample collected by heel or finger prick during child visits.…”
Section: Methodsmentioning
confidence: 99%
“…11 During the blood stage, iron deficiency may confer a protective effect by impairing the ability of Plasmodium falciparum to invade and propagate between erythrocytes. 12 In addition, recent experiments have also found that hepcidin-induced iron redistribution away from hepatocytes arrests the growth of intrahepatocytic parasites and thereby prevents the occurrence of malaria superinfections. 13 Epidemiological studies lend support to these findings: pregnant women and children who are iron deficient are observed to have lower risks of malarial disease, [14][15][16][17][18] and pediatric iron supplementation has been shown to heighten the risk of both clinical and severe malaria.…”
Section: Introductionmentioning
confidence: 99%
“…6,58 This fascinating hypothesis, requiring the development of a validated point-of-care hepcidin assay, is actively under evaluation. However, because iron-induced reticulocytosis could increase susceptibility to malaria, 76 and low hepcidin values do not necessarily exclude a concurrent infection, 46 safe iron supplementation in malaria-endemic areas should entail not only the ability to absorb and incorporate iron but also effective measures to prevent exacerbations of infections.…”
Section: Diagnosis and Management Of Idamentioning
confidence: 99%
“…RBCs were age separated using density gradient centrifugation 25 (detailed in supplemental Methods). ), were expressed and purified as described in the supplemental Methods.…”
Section: Isolation Of Differentially Aged Rbc Populationsmentioning
confidence: 99%